2020
DOI: 10.1002/advs.202001299
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Amyloid Beta Pathogenesis by Bacterial Amyloid FapC

Abstract: The gut–brain axis has attracted increasing attention in recent years, fueled by accumulating symptomatic, physiological, and pathological findings. In this study, the aggregation and toxicity of amyloid beta (Aβ), the pathogenic peptide associated with Alzheimer's disease (AD), seeded by FapC amyloid fragments (FapCS) of Pseudomonas aeruginosa that colonizes the gut microbiome through infections are examined. FapCS display favorable binding with Aβ and a catalytic capacity in seeding the peptide amyloidosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 106 publications
1
52
0
Order By: Relevance
“…As such, it is likely that bacteria may be secreting factors that translocate from the intestine across other tissues and affect proteostasis. A cross-seeding between disease-associated proteins (i.e., Aβ) with bacterial amyloids, including those from E. coli and P. aeruginosa, was previously observed [72,73]. Also, an enhancement of alpha-synuclein aggregation mediated by bacterial curli was shown in mouse and C. elegans Parkinson's disease models [74].…”
Section: Plos Pathogensmentioning
confidence: 84%
See 1 more Smart Citation
“…As such, it is likely that bacteria may be secreting factors that translocate from the intestine across other tissues and affect proteostasis. A cross-seeding between disease-associated proteins (i.e., Aβ) with bacterial amyloids, including those from E. coli and P. aeruginosa, was previously observed [72,73]. Also, an enhancement of alpha-synuclein aggregation mediated by bacterial curli was shown in mouse and C. elegans Parkinson's disease models [74].…”
Section: Plos Pathogensmentioning
confidence: 84%
“…coli and P . aeruginosa , was previously observed [ 72 , 73 ]. Also, an enhancement of alpha-synuclein aggregation mediated by bacterial curli was shown in mouse and C .…”
Section: Discussionmentioning
confidence: 95%
“…CsgA shares dissimilarity in sequences with Aβ 42 but is similar in triggering AD-related pathogenic effects and promoting cerebral plaque deposition [ 81 ]. In a recent study, Javed et al [ 92 ] claimed that FapCS favorably bound with Aβ, showed a catalytic capacity in seeding peptide amyloidosis, impaired cognitive performance, and behavior pathology in vitro, in silico and in a zebrafish AD model. Additionally, phenol soluble modulins contain cross-α structure and form cross-β fibrils associated with AD [ 93 ].…”
Section: Gm Dysbiosis and Admentioning
confidence: 99%
“…Higher levels of LPS and E. coli fragment K99 can promote myelin aggregates that colocalize with Aβ and resemble amyloid-like plaques. In addition, Javed et al (2020) found that FapC amyloid fragments (FapCS) of Pseudomonas aeruginosa display favorable binding with Aβ and a catalytic capacity to seed peptide amyloidosis, contributing to the aggregation and toxicity of Aβ. The robust seeding capacity for Aβ by FapCS and the biofilm fragments derived from P. aeruginosa entailed abnormal behavior pathology and immunohistology and impaired cognitive function in zebrafish.…”
Section: Alterations In Gut Microbiota In Patients With Admentioning
confidence: 99%